Group Differences and Similarities in Mental Representation Structure of Tennis Serve - Gromeier, Michael; Meier, Christopher; Schack, Thomas (Frontiers in Psychology, 2020)
A large number of studies have examined expertise and gender related differences in the mental representation of motor skills in different sports; throwing technique in judo (Weigelt, Ahlmeyer, Lex, & Schack, 2009), for frontloop in sailing (Schack 1999), and to the integration of routines in the mental movement representation in volleyball (Velentzas, Heinen, Tenenbaum, & Schack, 2010). Also, tactical behavioral studies were conducted in futsal (Linstromberg, Hennig, Heinen, Schack, & Frank, 2016) and football (Lex, Essig, Knoblauch, & Schack, 2015). In addition, studies to support the motor learning process through mental training by Frank et al. (2016) and Schack, Essig, Frank, and Koester (2014). The SDA-M was also used in the medical sector for the rehabilitation of stroke patients (Braun, Kleynen, Schols, Schack, Beurskens, & Wade, 2008). So far, few studies have investigated differences in the mental representation of a specific motor skill by experienced athletes of other related sports. The goal of the present study is to examine group differences and similarities in the mental representation of the tennis serve between experienced tennis, badminton, and handball athletes as well as a control group without any sport experience. We want to assess the quality of mental representation of technical-related overhead motion task expertises. For this purpose, we used the Structural Dimensional Analysis-Motoric method to measure the mental representation of the tennis serve of four different groups (tennis, badminton, and handball athletes and a group of novices). As expected, badminton, and handball athletes showed functionally well-structured representations, which were similar to the structure of the group of tennis athletes. Novices showed an unstructured mental representation. These outcomes confirm the relationship between mental representation and performance in the development of overhead motion. Furthermore, the results emphasis the importance of mental representations as an essential developmental aspect in learning motor skills, especially in learning technical-related motor skills.